Final Paleolithic in the Kaliningrad Region: current state of the study and source criticism based on published and archival data - Evgeniia Р. Tkach; Anzhela D. Malyarova; Artem S. Tarakanov (Археология евразийских степей)
Nowadays, the issues of human occupation of the South-Eastern Baltic, in particular, the territory of the Kaliningrad region, are poorly studied. However, the accumulation of knowledge about the initial appearance of human being in the region has a rich history. Finds belonging to the Final Paleolithic were first identified here as early as the beginning of the XX century. A detailed description of all materials belonging to the Stone Age was made by 1937. The variety of items made of bone and antler allowed researchers of the first half of the XX century to identify the initial stage of human occupation of the region using both typological and palynological methods. In the second half of the XX century, a series of locations with flint artifacts were discovered, and excavations were carried out systematically at one of them – Nikolskoye IV. Based on the results of AMS-dating of two reindeer antlers from the territory of the Kaliningrad region, the oldest dates for the South-Eastern Baltic were obtained, which refer to the last glacial maximum. The article presents brief results of the research in the XX–XXI centuries of the issues of human occupation of the Kaliningrad region according to archival and published data, and outlines prospects for further research.